Wave-packet dynamics in monolayer graphene with periodic scattering potentials - M.M. Suleimanov (22921019) (2025)
We use the Dirac continuum model to study the propagation of electronic wave packets in monolayer graphene in the presence of periodically arranged circular potential steps. The time propagation of the wave packets is calculated using the split-operator method for different sizes, heights, and separations of the barriers. We found that, despite the pronounced Klein tunneling effect in graphene, the presence of a lattice of defects significantly impacts the propagation properties of the wave packets. For example, depending on the height and size of the incident wave packet, the transmission probability can decrease by more than 30%. The alteration of the polarity of the potential barriers also contributes to the transmission probabilities of the wave packets in graphene. The results obtained her e provide valuable insights into the fundamental understanding of charge carrier dynamics in graphene-based nanodevices. Other Information Published in: Physica B: Condensed Matter License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.physb.2025.417484